Optimalisasi Fungsi Pigmen Bunga Mawar Sortiran Sebagai Zat Pewarna Alami Dan Bioaktif Pada Produk Industri - Elfi Anis Saati; Theovilla RRD; Simon Bambang Widjanarko; A Aulanni'am (Department Industrial Engineering, University of Muhammadiyah Malang, 2011)
The roses known to contain anthocyanins pigments and as a bioactive compound which can act as free radical catcher material. When harvest season arrives in number will be very abundant. Flowers sorting which can decrease the selling price can be processed in the form of natural dyes for food, cosmetics and medicines / herbs. The purpose of this study is to know applications rose to the quality of some industrial products. The experiment was conducted in (fresh, 2 and 4 days), that performed using randomized block design. Phase II is the application of pigment products of red roses on some industrial products (ie food products, herbal and cosmetics), using the design in accordance with their respective target. The results showed that ucts such as fruit juice, yoghurt, jelly, carbonated beverage (food) and body lotion (cosmetic), and can contribute to the natural color at a time serves as a source of bioactive in effervescent tablets.